Perselingkuhan dan Relasi Sosial Modern: Tindakan Preventif dalam Tafsir Ibnu Katsir dan Hadis “Ipar Adalah Maut” - Sefri Auliya; Hidayatul Azizah Azizah Gazali; Afzico Muhammad Chandra; Desri Nengsih; Winda Meri Susila (Lathaif: Literasi Tafsir, Hadis dan Filologi, 2026)
The transformation of social relations in the digital era has reshaped patterns of interaction between men and women, increasing opportunities for infidelity through both direct and digital communication. This study aims to examine Islamic preventive measures against infidelity based on Ibn Kathīr’s interpretation of Qur'an Surah An-Nūr (24):31 and the prophetic tradition (ḥadīth) al-ḥamwu al-mawt ("the in-law is death"), as well as their relevance to contemporary social relationships. This study employs a qualitative library research approach. The primary sources consist of Tafsīr al-Qur'ān al-'Aẓīm by Ibn Kathīr, Qur'an Surah An-Nūr (24):31, and the ḥadīth al-ḥamwu al-mawt, while the secondary sources include Qur'anic exegesis, ḥadīth literature, and relevant scholarly publications. Data were analyzed using content analysis through the stages of data reduction, thematic categorization, interpretation, and synthesis. The findings reveal that Ibn Kathīr positions Qur'an Surah An-Nūr (24):31 and the ḥadīth al-ḥamwu al-mawt as fundamental preventive principles for safeguarding personal chastity and family resilience through lowering the gaze, preserving modesty, regulating interactions with non-maḥram individuals, and avoiding situations that may lead to moral temptation (fitnah). The study further demonstrates that these Qur'anic and prophetic principles remain highly relevant in addressing contemporary challenges, including digital communication and emotional infidelity. This study contributes by contextualizing Ibn Kathīr's interpretation and the ḥadīth al-ḥamwu al-mawt as an ethical-preventive framework for responding to the phenomenon of infidelity in modern society.